The Impact Of Green Supply Chain Management Practices On Firm’s Competitive Advantages. - Alhussain Alsuraihi; Khairul Affeiq Mohd. Noorizam; Rosnia Masruk; Ab Rahman,Z.; Norailis Ab Wahab (Universidad Tecnica de Manabi, 2024)
Non-Indexed Publication